2011
DOI: 10.1111/j.1365-2664.2011.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to sustainable frankincense production: blocked regeneration, high adult mortality and declining populations

Abstract: Summary 1.Resins are highly valued non-timber forest products (NTFP). One of the most widely traded resins is frankincense, tapped from several Boswellia tree species (Burseraceae). Exploited Boswellia populations often show poor regeneration, but the demographic consequences of these bottlenecks are unknown. Here we report on the first large-scale demographic study of frankincense-producing trees. 2. We studied 12 populations of Boswellia papyrifera in northern Ethiopia, varying in altitude and productivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 26 publications
2
46
2
1
Order By: Relevance
“…The population was characterized by patches of abundant seedlings and saplings and a few small and big-sized adult trees. Unlike Groenendijk et al (2012) in the population in Metema, in the North of Ethiopia, we observed that several small B. papyrifera individuals as tall as only 1.5 m were already flowering in this population.…”
Section: Study Area and Samplingcontrasting
confidence: 87%
See 2 more Smart Citations
“…The population was characterized by patches of abundant seedlings and saplings and a few small and big-sized adult trees. Unlike Groenendijk et al (2012) in the population in Metema, in the North of Ethiopia, we observed that several small B. papyrifera individuals as tall as only 1.5 m were already flowering in this population.…”
Section: Study Area and Samplingcontrasting
confidence: 87%
“…The two populations were treated as replications for the FSGS analysis of the species. All four life cycles/size classes described in Groenendijk et al (2012) were present simultaneously in these two populations, although the relative abundance differed between the two populations.…”
Section: Study Area and Samplingmentioning
confidence: 90%
See 1 more Smart Citation
“…The annual rainfall of Metema ranges from 660-1100 mm with mean annual rainfall of about 884 mm (Groenendijk et al, 2012). Metema has a uni-modal rainfall pattern.…”
Section: Study Sitementioning
confidence: 99%
“…Based on this transformation, the population dynamics of A. malybo was described as in standard matrix models: n(t + 1) = K n(t). [ 111 ] population growth rate (λ t ) was calculated as in Groenendijk et al (2012):…”
Section: Integral Projection Models (Ipm)mentioning
confidence: 99%